El silencio administrativo negativo y su vulneración al Art. 76 numeral 7 literal l de la Constitución de la República del Ecuador - Villavicencio Montoya, Evanna Valeria (2024)
This article is the result of the research carried out to determine whether the fictitious figure called negative administrative silence violates the Constitutional guarantee, of the right of defense and having motivated administrative resolutions and acts. Specifically, an analysis was made with respect to the extraordinary appeal for review and whether Art. 234 of the Organic Administrative Code, which establishes that if within a period of one month the administration does not answer the extraordinary appeal filed, it must be understood as abandoned and consequently, the administrative process has been exhausted without having a resolution or administrative act to be challenged it in the jurisdictional process by virtue of Art. 308 of the General Organic Code of Procedure. Through research and interpretation of the regulations in force, as well as interviews with two judges who make up the administrative and tax courts of the canton and province of Loja, it was determined that the negative administrative silence has become positive, leaving exceptions to apply the negative effect, stating that maintaining this fictitious figure would be contrary to the evolution of the law. In view of this, the extraordinary recourse of review is part of this exception and with it, it will be determined if maintaining this negative effect violates the right to defense established in Art. 76 numeral 7 of the Constitution of the Republic of Ecuador.